2006
DOI: 10.1111/j.1530-0277.2006.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin Is Down‐regulated in Alcoholic Liver Injury: Implications for the Pathogenesis of Alcoholic Liver Disease

Abstract: The down-regulation of hepcidin and C/EBPalpha gene expression shown in vivo implies disturbed iron sensing contributing to the hepatosiderosis seen in alcoholic liver disease, possibly by mechanisms involving the IL-6 signaling cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 41 publications
5
104
2
3
Order By: Relevance
“…10,11 As for the contribution of nongenetic factors, ethanol abuse (long associated with iron overload) is now believed to inhibit hepcidin transcription. 12,13 Similar effects can be produced by toxic and viral insults (for example, the hepatitis C virus may inhibit hepcidin expression 14 ). The unexplained hepatic iron overload associated with acute liver failure and chronic end-stage liver disease, which closely resembles that of hemochromatosis, 15 may be a manifestation of diminished hepcidin output due to a markedly reduced functional hepatic mass.…”
Section: Disruption Of Homeostasis: Insulin and Diabetes Hepcidin Anmentioning
confidence: 98%
“…10,11 As for the contribution of nongenetic factors, ethanol abuse (long associated with iron overload) is now believed to inhibit hepcidin transcription. 12,13 Similar effects can be produced by toxic and viral insults (for example, the hepatitis C virus may inhibit hepcidin expression 14 ). The unexplained hepatic iron overload associated with acute liver failure and chronic end-stage liver disease, which closely resembles that of hemochromatosis, 15 may be a manifestation of diminished hepcidin output due to a markedly reduced functional hepatic mass.…”
Section: Disruption Of Homeostasis: Insulin and Diabetes Hepcidin Anmentioning
confidence: 98%
“…Recently, it has been shown that alcohol down-regulates hepcidin transcription, which leads to increased duodenal iron absorption via a divalent metal transporter-1 (with enhanced luminal import) and ferroportin protein expression (with enhanced basolateral translocation to the circulation) [7,8] . Furthermore, it has been shown that alcohol abolishes the iron-induced upregulation of both liver hepcidin transcription and the DNA-binding activity of C/EBP alpha [9] , thus negating the protective effect of hepcidin.…”
Section: Introductionmentioning
confidence: 99%
“…19 Oxidative stress in the liver secondary to alcohol or chronic viral hepatitis can lead to suppression of hepcidin, leading to excess iron accumulation and progression of underlying disease. 20,21 4. Correct Answers: A, D, and E Intrahepatic cholestasis of pregnancy (ICP) classically presents in the third trimester with pruritus, raised serum bile acids, and spontaneous resolution after delivery.…”
Section: Correct Answers: a B And Cmentioning
confidence: 99%